Pengaruh Kepemilikan Manajerial, Kebijakan Hutang dan Profitabilitas terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Manufaktur Sub sektor Industri Barang Konsumsi) yang terdaftar di Bursa Efek Indonesia Tahun 2015-2017 - Aminatun Nasukha; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
AbstractThis research was conducted to examine the effect of managerial ownership, debt policy and profitability on the firm value of sub-sectional manufacturing companies of the consumer goods industry listed on the Indonesia Stock Exchange in 2015-2017.The population used in this study is the consumer goods manufacturing sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2015-2017. The sampling method is purposive sampling according to predetermined criteria. The number of samples is 27 companies. The data in this study used multiple linear regression, classical assumption and hypothesis test.The results of this study indicate that managerial ownership has  negative in significant effect on firm value, debt policy has negative significant effect on firm value and profitability has positive significant effect on firm value. Keywords: Managerial Ownership, Debt Policy, Profitability, Firm Value.